Legal Protection for Small Businesses in the Free Market Era in Indonesia Review of Law Number 20 of 2008 concerning Micro Small and Medium Enterprises - Widiarty, Wiwik Sri (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Implementing the free market in the ASEAN region is one way to grow an advanced economy. Entrepreneurs must be able to compete in this free market era, including small businesses in Indonesia. Small businesses in Indonesia have an essential role in social welfare and economic development in Indonesia. Therefore, the presence of small businesses must be protected because small businesses are absorption of labor. For this reason, a problem must be answered: how to provide legal protection for small businesses in Indonesia's free market era. Meanwhile, the research method used in this study is a normative legal research method, namely library law research conducted by examining library materials or mere secondary data. This research resulted in a conclusion that legal protection is essential to be provided by the government for MSMEs in Indonesia so that there is legal certainty in guaranteeing the activities of small business actors; several Laws and Invitations have been issued which regulate them among others, the MSME Law, and Law No. 7 of 1994 concerning the Agreement Establishing the World Trade Organization.